Global political instability as a factor of international tourism - Ткачук, Л. (Київський національний університет імені Тараса Шевченка, 2018)
The article is devoted to the disclosure the ways in which the global international political instability influence the international tourism. In particular, the components of global international political instability are described and indices that determine the level of security and threats in different countries of the world are analyzed. Political stability and safety are prerequisites for tourism; even the threat of events such as civil unrest and terrorism can cause tourists to rethink their decision to visit a destination. In order to evaluate how different components of geopolitical instability influence on international tourism, the results of surveys of consumer behaviour of tourists for different years are analyzed. Terrorism is identified as the most alarming for travellers type of geopolitical factors. Over 40% of all international travellers plan to change their travel behaviour due to terror concerns. The safest and dangerous, from the tourists point of view, destinations are disclosed. Destinations such as Turkey, Egypt and Tunisia which have all suffered terror attacks in recent years are still seen as particularly unsafe. And the USA and the UK are new on the list of ‘potentially endangered’ destinations. It is proposed to consider the global instability as the geopolitical risks of international tourism because of unpredictable of its effect for different tourist destinations. The geopolitical risk for tourism is defined as the risk associated with wars, terrorist acts, and tensions between states that affect international tourism. Countries affected by political unrest inevitably experience a decline in the number of international tourists and tourism receipts however on different scales. On the other hand, some destinations which are seen as particularly safe could thus benefit from the travellers who shift destinations due to the terrorist threat. Recommendations on levelling negative effects of geopolitical instability for tourist demand are formulated. The course of action should be targeted at four key fields: crisis management, incentives for tourists, perception management and rebranding of the tourism destination.

Стаття присвячена висвітлено механізмів впливу глобальної геополітичної нестабільності на міжнародний туризм. Зокрема, схарактеризовано складові глобальної геополітичної нестабільності, розглянуто індекси, що відображають рівень безпеки та загроз в різних країнах світу. Для оцінки впливу складових геополітичної нестабільності на міжнародний туризм проаналізовано результати досліджень споживацької поведінки туристів за різні роки; визначені види політичних конфронтацій, що найбільше турбують подорожуючих; названі найбільш безпечні та небезпечні туристичні напрями. Пропонується розглядати глобальну нестабільність в якості геополітичних ризиків міжнародного туризму.
Глобальна геополітична нестабільність як чинник розвитку міжнародного туризму
1. Ткачук Л.М. Вплив політичної нестабільності на розвиток туристичної дестинації / Ткачук Л.М. // Географія та туризм: наук. зб. – К., 2016. – Вип. 37. – С. 26-36. 2. Baker D. The Effects of Terrorism on the Travel and Tourism Industry / D. Baker // International Journal of Religious Tourism and Pilgrimage. – 2014. – Volume 2(1). – Рр. 57-67. 3. Fragile States Index 2017 / Fund for Peace. – [Електронний ресурс]. – Режим доступу: http://www.fundforpeace.org/fsi/ 4. Global Peace Index 2017. – [Електронний ресурс]. – Режим доступу: http:// www.visionofhumanity.org/indexes/global-peace-index/ 5. Global Terrorism Index 2017– [Електронний ресурс]. – Режим доступу: http:// www.visionofhumanity.org/indexes/terrorism-index/ 6. How to Re-emerge as a Tourism Destination after a Period of Political Instability / Haddad C., Nasr A., Ghida E., Al Ibrahim H. // Travel & Tourism Competitiveness Report 2015. – Pp. 53-57. 7. Sönmez S. Tourism, Terrorism and Political Instability / S.F Sönmez // Annals of Tourism Research. – 1998. – Vol. 25:2. – Pp. 416-456. 8. The state of play, the impact of geopolitical events on international tourism in 2017 / Morakabati Y., Fletcher J., Beavis J.// ITB Berlin 2017. – [Електронний ресурс]. – Режим доступу: https://www.itb-berlin.de/media/itb/itb_dl_en/itb_itb_berlin_en/itb_itb_academy_en/Travelzoo_Studie_ITB_2017.pdf 9. UNWTO Tourism Highlights 2017 Edition. – [Електронний ресурс]. – Режим доступу: https://www.e-unwto.org/doi/pdf/10.18111/9789284419029
Keywords: туризм; безпека туристичної подорожі; політична нестабільність; тероризм; геополітичні ризики в туризмі; tourism; the safety of travel; political instability; terrorism; geopolitical risks for tourism